Melothesia in Babylonia : medicine, magic, and astrology in the ancient Near East - Geller, Markham J. (Science, technology, and medicine in ancient cultures ;, 2014)
This book examines the Babylonian backgroundof melothesia, the science of charting zodiac influences on the human body, which transformed older divination by connecting astrology with medical techniques. Special attention is given to a text from late-5th-century Uruk, which is argued to be an important representative of this new approach to the healing arts, previously only known from Greek and medieval astrology.